Generalized Fractional-Order Discrete-Time Integrator - Dorota Mozyrska; Piotr Ostalczyk (Complexity)
We investigate a generalization of discrete-time integrator. Proposed linear discrete-time integrator is characterised by the variable, fractional order of integration/summation. Graphical illustrations of an analysis of particular vector matrices are presented. In numerical examples, we show relations between the order functions and element responses.